PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP PENINGKATAN HASIL BELAJAR PADA RANAH KOGNITIF, AFEKTIF DAN PSIKOMOTORIK PADA MATA PELAJARAN AGAMA HINDU SISWA KELAS XI TSM 3 SMKN 3 SINGARAJA: The Application of Contextual Teaching and Learning (CTL) Model to Improve Learning Outcomes in Cognitive, Affective, and Psychomotor Domains in Hindu Religious Education for Class XI TSM 3 Students at SMKN 3 Singaraja. - Tika Indriani, Ni Luh Putu; Prapnuwanti, Ni Luh Purnamasuari; pitriani, Ni Rai Vivien (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
AbstractThis study is a Classroom Action Research (CAR) conducted during teaching practice activities over a period of three months in the odd semester (Block 1), from July to September 2024, with the researcher acting as the teacher implementing the learning process. The study aimed to improve students’ learning outcomes in Hindu Religious Education across the cognitive, affective, and psychomotor domains through the application of the Contextual Teaching and Learning (CTL) model. The research subjects consisted of 22 students of Phase F/Grade XI TSM 3 at SMKN 3 Singaraja. The research was carried out in two cycles, each comprising the stages of planning, action implementation, observation, and reflection. Data were collected through learning outcome tests, observation, and documentation. Data analysis was conducted descriptively by examining the mean scores and the percentage of learning mastery.The results indicated an improvement in students’ learning outcomes in the cognitive domain. In the pre-cycle stage, the average score was 50 with a mastery percentage of 23%. This increased in Cycle I to an average score of 56 with 45% mastery, and further improved significantly in Cycle II to an average score of 80.6 with a mastery percentage of 91%. In the affective domain, students’ learning outcomes in the pre-cycle were categorized as low, with an average score of 1.75. In Cycle I, the score increased to 2.1 in the fair category, and in Cycle II it improved to 3.0 in the good category. This improvement indicates the development of students’ attitudes, activeness, and participation in the learning process. In the psychomotor domain, the pre-cycle results were categorized as low, with an average score of 1.58. In Cycle I, the score increased to 2.7 in the good category, and in Cycle II it reached 3.5 in the very good category. Based on these findings, it can be concluded that the application of the Contextual Teaching and Learning (CTL) model is effective in improving learning outcomes in Hindu Religious Education for Grade XI TSM 3 students of SMKN 3 Singaraja across the cognitive, affective, and psychomotor domains. Keywords: Contextual Teaching and Learning (CTL), Hindu Religious Education Learning Outcomes, Classroom Action Research (CAR)